Memahami Pancasila dalam Algoritma Media Sosial: Analisis Wacana Digital Tentang Ideologi Bangsa - Ahmad Muhamad Musain Nasoha; Ashfiyah Nur Atqiyah; Miftahul Mujahidin; Raynar Andaru Ahnaf; Nafilah Zahratun jannah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The evolution of social media and its algorithms has transformed the dissemination of Pancasila as Indonesia’s national ideology. This study aims to analyze the representation of Pancasila in algorithmically curated digital discourse and its impact on public understanding. A qualitative approach, combining digital discourse analysis and netnography, was applied to examine content on Twitter, Facebook, Instagram, and YouTube. Findings reveal the dual role of social media algorithms: while facilitating educational content on Pancasila (e.g., religious tolerance, human rights campaigns, and nationalism), they also amplify polarizing content, hoaxes, and hate speech that contradict Pancasila values. Analysis of Pancasila’s five principles shows that conflict-driven content (e.g., ethnic-religious issues) gains higher virality due to algorithms’ prioritization of engagement metrics. The filter bubble and echo chamber phenomena exacerbate discourse fragmentation, hindering inclusive dialogue about national ideology. The study concludes that Pancasila-based digital literacy, algorithmic transparency, and multistakeholder collaboration are critical to optimizing social media’s role in strengthening national identity. Policy recommendations include integrating "social cohesion" parameters into algorithm design and regulating content to uphold diversity.